2011
DOI: 10.1097/sla.0b013e3181ff461f
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Effectiveness of Surgical Scalpel or Diathermy in Making Abdominal Skin Incisions

Abstract: Diathermy incisions are equally prone to get wound infection, as do the incisions made with scalpel. Furthermore, lower incidence of early postoperative pain, swiftness of the technique, and a reduced blood loss are the encouraging facts supporting routine use of diathermy for abdominal skin incisions after taking careful precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
(50 reference statements)
6
26
2
2
Order By: Relevance
“…A review of the pertinent surgical literature demonstrates several large-scale studies that have examined the rates of wound infection between abdominal wall and groin skin incisions made with a knife and a standard pen electrode on cutting mode; the general consensus is that there is no significant difference between the 2 modalities in terms of postoperative wound complications. [7][8][9][10][11][12][13] To assess cosmetic outcomes, Stupart et al 14 compared abdominal incisions made with scalpel and monopolar cutting diathermy, without specifying the type of cautery tip, as judged by the patient, and found no difference between the 2 methods. Several other studies have found that the use of electrocautery for skin incision decreases incision time and blood loss 9,11-13,15 as well as acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the pertinent surgical literature demonstrates several large-scale studies that have examined the rates of wound infection between abdominal wall and groin skin incisions made with a knife and a standard pen electrode on cutting mode; the general consensus is that there is no significant difference between the 2 modalities in terms of postoperative wound complications. [7][8][9][10][11][12][13] To assess cosmetic outcomes, Stupart et al 14 compared abdominal incisions made with scalpel and monopolar cutting diathermy, without specifying the type of cautery tip, as judged by the patient, and found no difference between the 2 methods. Several other studies have found that the use of electrocautery for skin incision decreases incision time and blood loss 9,11-13,15 as well as acute postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that diathermy incision is quick and has reduced blood loss and reduced early post-operative pain [6].…”
Section: High-frequency Surgical Equipmentmentioning
confidence: 97%
“…Aber auch die Technik der Laparotomie kann zu einer Reduktion der Schmerzempfindung führen. Die Verwendung von Diathermiestrom bei der Hautinzision, kann in den ersten 24 h die Schmerzempfindung reduzieren, ohne die Quote der Wundinfektionen zu erhöhen [1]. Im Rahmen der MIC wird als Bergelaparotomie die transversale Laparotomie bevorzugt wegen deutlich geringerer postoperativer Schmerzen verglichen mit der medianen Laparotomie [7].…”
Section: Perioperative Schmerztherapieunclassified